Analisis Kepemimpinan Kepala Sekolah dalam Supervisi Pembelajaran Guru Pendidikan Agama Islam Berdasarkan Kurikulum 2013 di Sekolah Menengah Atas Negeri 1 Percut Sei Tuan - Rahmadani, Putri Suci; Syahputri, Nurtika; Kusworo, Singgih; Neliwati, Neliwati (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This type of research is descriptive qualitative. The approaches used in this research are: (a.) Paedagogic Approach (b.) Management Approach c.) Psychological Approach. Sources of data used in this study are: Primary Sources, Secondary Sources. Data collection techniques are Observation, Interview and Documentation and data analysis techniques used are: Data Reduction, Data Presentation, and Drawing Conclusions/Verification. The results of this study found that the leadership of the principal at SMAN 1 Percut Sei Tuan, which is often used by the principal is the type of communication leadership to shape teachers to become professional teachers in their respective fields, in the opinion of some teachers, that during his term of office the principal schools often give assumptions or directions to their subordinates, to always encourage them to carry out activities according to the functions of each teacher and also staff, so that the implementation of teacher learning can be carried out properly, and also as staff always carry out operations in accordance with the functions and directions of the school principal. So that a good cooperative relationship arises between the principal and his subordinates, and this will become the basis or reference for the principal to make a quality education system in accordance with the vision and mission at SMAN 1 Percut Sei Tuan.